1978
DOI: 10.1056/nejm197805042981804
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin-D-Dependent Rickets Type II

Abstract: Studies were done to determine the cause for hypocalcemia, secondary hyperparathyroidism, osteomalacia and osteitis fibrosa cystica in a 22-year-old black woman. The patient had normal serum 25-hydroxyvitamin D (14 ng per milliliter) and markedly elevated serum 1,25-dihydroxyvitamin D (137 pg per milliliter). Vitamin D3, 4000 units per day for four weeks, increased the serum 25-hydroxyvitamin D and 1,25-dihydroxyvitamin D to as high as 29 and 297 pg per milliliter, respectively, and corrected the hypocalcemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(35 citation statements)
references
References 19 publications
1
33
0
1
Order By: Relevance
“…A similar cross talk mechanism was proposed for PXR/constitutive androstane receptor and VDR (Drocourt et al, 2002). Such regulatory overlap may have implications for treatment of conditions in which the function of a hormonal nuclear receptor is altered, such as the thyroid hormone resistance syndrome, linked to mutations in TR (Sakurai et al, 1989), or vitamin D-resistant rickets, in which a mutated VDR does not respond to Vit D 3 (Brooks et al, 1978). If orphan nuclear receptors in the presence of specific therapeutic agents increased the expression of genes that are normally regulated by the defective hormonal nuclear receptor, this could provide a paradigm for amelioration of specific clinical or physiologic manifestations of these conditions.…”
Section: Levothyroxine Upregulates P-gpmentioning
confidence: 99%
“…A similar cross talk mechanism was proposed for PXR/constitutive androstane receptor and VDR (Drocourt et al, 2002). Such regulatory overlap may have implications for treatment of conditions in which the function of a hormonal nuclear receptor is altered, such as the thyroid hormone resistance syndrome, linked to mutations in TR (Sakurai et al, 1989), or vitamin D-resistant rickets, in which a mutated VDR does not respond to Vit D 3 (Brooks et al, 1978). If orphan nuclear receptors in the presence of specific therapeutic agents increased the expression of genes that are normally regulated by the defective hormonal nuclear receptor, this could provide a paradigm for amelioration of specific clinical or physiologic manifestations of these conditions.…”
Section: Levothyroxine Upregulates P-gpmentioning
confidence: 99%
“…Whatever the basic molecular defect(s), the accumulating data clearly show a great heterogeneity in the clinical features ofpatients with hereditary resistance to 1,25(OH)2D and in their response to therapy with vitamin D derivatives (1). Favorable clinical responses to the administration ofpharmacological doses of native vitamin D, 25(OH)D3, la(OH)D3, 1,25(OH)2D3 (3)(4)(5)(6)(7)(8)(9)(10), or 24,25(OH)2D3 (11) have been reported in some patients. However, it has been shown that other patients with resistance to 1,25(0H)2D3 may remain unresponsive to similar therapeutic trials (10,12,13) or, after prolonged remission oftheir symptoms, become completely refractory to treatment with vitamin D derivatives (10).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of a functional receptor is clearly demonstrated through the disease vitamin D-dependent rickets type II (5,6). Patients with this disease suffer impaired calcium absorption despite high circulating levels of 1,25-dihydroxyvitamin D3.…”
mentioning
confidence: 99%